THE RELATIONSHIP OF SOCIAL SECURITY WITH OTHER SECTORS (World Bulletin of Education and Learning, 2025)
Social security is one of the important sectors of society, which is a systematic activity aimed at improving the quality of life of people, ensuring their social security and implementing social justice. The effective functioning of social security is closely related to many other sectors, and their interaction is an important factor in the sustainable development of society. This article provides information on the relationship of social security with other sectors, their influence on each other and their interdependence.
Keywords: Social security, society, economy, economic stability, crisis, budget, justice, information and communication technologies, modern technologies.